Disability and the Goods of Life. Issue 6 (2nd December 2021) - Campbell, Stephen M; Nyholm, Sven; Walter, Jennifer K
Abstract: The so-called Disability Paradox arises from the apparent tension between the popular view that disability leads to low well-being and the relatively high life-satisfaction reports of disabled people. Our aim in this essay is to make some progress toward dissolving this alleged paradox by exploring the relationship between disability and various "goods of life"—that is, components of a life that typically make a person's life go better for them. We focus on four widely recognized goods of life (happiness, rewarding relationships, knowledge, achievement) and four common types of disability (sensory, mobility, intellectual, and social) and systematically examine the extent to which the four disability types are in principle compatible with obtaining the four goods of life. Our findings suggest that there is a high degree of compatibility. This undermines the widespread view that disabilities, by their very nature, substantially limit a person's ability to access the goods of life, and it provides some guidance on how to dissolve the Disability Paradox.